👤

(x+1)²-3(x+7)=3+(x-2)²
(3x-1)²-5(x+2)(x-2)=(2x+3)²+6
(x+2)²/6-(x-2)²/5=4x+7/15-(x-2)(x+2)-5/30


Răspuns :

a) [tex] x^{2} [/tex]+2x+1 -3x-21=3+[tex] x^{2} [/tex]-4x+4
[tex] x^{2} [/tex]-x-20=7+[tex] x^{2} [/tex]-4x
[tex] x^{2} [/tex]-[tex] x^{2} [/tex]-x+4x=7+20
3x=27
x=9

b)[tex] 9x^{2} [/tex]-6x+1-5([tex] x^{2} [/tex]-4)=[tex] 4x^{2} [/tex]+12x+9+6
[tex] 9x^{2} [/tex]-6x+1-[tex] 5x^{2} [/tex]+20=[tex] 4x^{2} [/tex]+12x+15
[tex] -4x^{2} [/tex]-6x+21=[tex] 4x^{2} [/tex]+12x+15
[tex] -4x^{2} [/tex]-[tex] 4x^{2} [/tex]-6x-12x=15-21
-18x=-6
18x=6
x=3